Variations of retinal dysfunctions with the level of cannabis use in regular users: Toward a better understanding of cannabis use pathophysiology - Schwitzer, Thomas; Moreno-Zaragoza, Aldo; Dramé, Louis; Schwan, Raymund; Angioi-Duprez, Karine; Albuisson, Eliane; Laprévote, Vincent (Frontiers in Psychiatry, 2022)
The impact of regular cannabis use on retinal function has already been studied using flash (fERG) and pattern (PERG) electroretinogram. Delayed ganglion and bipolar cells responses were observed as showed by increased peak time of PERG N95 and fERG b-wave recorded in photopic condition. Hypoactivity of amacrine cells was also showed by decreased amplitudes of oscillatory potentials (OPs). However, it is unknown how these retinal anomalies evolve according to the level of cannabis use in cannabis users. The aim of this study was to longitudinally assess the retinal function during a treatment aiming to reduce cannabis use. We recorded PERG and fERG in 40 regular cannabis users receiving either an 8-week mindfulness-based relapse prevention program or an 8-week treatment-as-usual therapy. ERGs were recorded before treatment, at the end of it, and four weeks afterwards. We found reduced peak times in PERG N95 and fERG b-wave (p = 0,032 and p = 0,024: Dunn’s post hoc test) recorded at week 8 and increased amplitudes in OP2 and OP3 (p = 0,012 and p = 0,030: Dunn’s post hoc test) recorded at week 12 in users with decreased cannabis use. These results support variations of retinal anomalies with the level of cannabis use, implying that reduction of cannabis use could restore retinal function in regular users.